2015
DOI: 10.7314/apjcp.2015.16.12.5049
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Breast Cancer in Iranian Women is Increasing

Abstract: Background: Breast cancer (BC) is the leading cause of oncological death for women, in both developed and developing countries. In Iran, breast cancer ranks first among cancers diagnosed in women. The aim of this study was to present the burden of this cancer including incidence, mortality and years life lost (YLL) due to breast cancer in Iranian women. Materials and Methods: National incidence data from the Iranian annual National Cancer Registration reports from 2003 to 2009 and national death statistics rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 31 publications
3
47
2
Order By: Relevance
“…In Iran, no national screening program for BC is done and studies showed that women awareness of the warning and effective signs is very inadequate (Yavari and Pourhoseingholi, 2007;Montazeri et al, 2008). In addition, the health learning program for women in Iran in order to reduce the lack of women awareness about BC will be beneficial to control the cancer burden in the future (Sharifian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Iran, no national screening program for BC is done and studies showed that women awareness of the warning and effective signs is very inadequate (Yavari and Pourhoseingholi, 2007;Montazeri et al, 2008). In addition, the health learning program for women in Iran in order to reduce the lack of women awareness about BC will be beneficial to control the cancer burden in the future (Sharifian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…BC has the first rank among diagnosed cancers in Iranian women. The overall mortality rate of BC during the ears 1990, 1995, 2000, 2005 and 2010 has increased from 0.96 to 4.33 per 100,000 people and also the incidence rate increased from 16.0 to 28.3 per 100,000 people during the study year (Sharifian et al, 2015). Female diseases and BC include 7.8% and 25.6% of all cancers in women in Iran, respectively, and these values are lower compared to other countries (Arab et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It's the most common cancer in Iranian women with a mortality rate of 2614 cases per year (Jafari et al, 2014;Sharifian et al, 2015). Early detection of that would be helpful for its successful treatment.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the general mortality rate of breast cancer has increased during these years from 0.96 to 4.33 per 100,000 and the incidence rate increased from 16.0 to 28.3 per 100,000 for the years under study, concluding that the burden of breast cancer for Iranian women is still increasing (4).…”
Section: Introductionmentioning
confidence: 99%